Leadership Strategies of Darussalam Gontor Islamic Boarding School in Facing the Global Era - Mujahada, Kharis Syuhud; Kurnia, Heri (Innovations in Multidisciplinary Education Journal, 2025)
The era of globalization presents significant challenges for Islamic educational institutions, particularly traditional Islamic boarding schools (pesantren), which must balance the preservation of Islamic values with adaptation to global demands. This study aims to analyze the leadership strategies employed by Pondok Pesantren Darussalam Gontor in facing the global era while maintaining its Islamic identity and educational quality. The research employed a qualitative methodology with a phenomenological research design, conducted as a field study at the modern Islamic boarding school of Darussalam Gontor in Ponorogo, East Java. Data were collected through in-depth interviews with 15 key informants including the leadership board, senior teachers (ustadz), and alumni, supplemented by participant observation and document analysis over a six-month period from January to June 2024. The findings reveal that Gontor implements a multi-dimensional leadership strategy encompassing five key areas: curriculum integration that combines traditional Islamic studies with modern sciences at a 60:40 ratio, technological adaptation through digital learning platforms used by 95% of students, international networking with 127 affiliated institutions across 18 countries, alumni empowerment programs reaching over 80,000 graduates worldwide, and sustainable institutional development with annual growth rates of 8-12% in student enrollment. The leadership adopts a transformational approach that emphasizes vision alignment, cultural preservation, and adaptive innovation. The study concludes that Gontor's success in navigating globalization stems from its ability to maintain core Islamic values while embracing selective modernization, creating a unique educational model that produces globally competitive graduates who remain firmly rooted in Islamic principles and Indonesian cultural identity.